BUDAYA NUANSA RELIGIUS PESANTREN DALAM MEMBENTUK KARAKTER SANTRI - Ahmad Fauzi (Pascasarjana Institut Agama Islam Al-Qolam, 2023)
As part of society, pesantren with the core values ​​of kiai, santri, mosque, pondok, and the yellow book have developed into their own subculture. Therefore, despite modernization and globalization, pesantren remain conservative. In addition, many stakeholders agree that pesantren can be a strong example of character-based education in Indonesia. There are many questions that should be discussed in this research, namely how to plan and carry out character building exercises that are used by pesantren administrators or teachers to form student or santri subcultures and what form they take. This study uses qualitative research to gain attention within the Islamic boarding school itself. Keywords: Religious, Character, Culture, Islamic Boarding School